Altered Expression of ORAI and STIM Isoforms in Activated Human Cardiac Fibroblasts - Čendula, R; Chomaničová, N; Adamičková, A; Gažová, A; Kyselovič, J; Máťuš, M (Physiological research, 2021)
Cardiac fibrotization is a well-known process characteristic of many cardiac pathological conditions. The key element is excessive activation of cardiac fibroblasts, their transdifferentiation into myofibroblasts, increased production, and accumulation of extracellular matrix proteins, resulting in cardiac stiffness. The exact cellular mechanisms and molecular components involved in the process are not fully elucidated, but the SOCE mechanism could play an important role. Its key molecules are the molecular sensor of calcium in ER/SR - STIM and the highly selective calcium channels Orai located in the plasma membrane. This study aims to evaluate selected SOCE-associated genes in the activation of HCF cell culture by several known substances (phenylephrine, isoprenaline) that represent cardiovascular overload. After cell cultivation, cell medium was collected to measure the soluble collagen content. From the harvested cells, qRT-PCR was performed to determine the mRNA levels of the corresponding genes. The activation of cells was based on changes in the relative expression of collagen genes as well as the collagen content in the medium of the cell culture. We detected an increase in the expression of the Orai2 isoform, a change in the Orai1/Orai3 ratio and also an increase in the expression of the STIM2 isoform. These results suggest an increased activation of the SOCE mechanism under stress conditions of fibroblasts, which supports the hypothesis of fibroblast activation in pathological processes by altering calcium homeostasis through the SOCE mechanism.
Keywords: lidé; Protein Isoforms; protein - isoformy; kanály aktivované uvolněním vápníku; Stromal Interaction Molecules; Cells, Cultured; proteiny STIM; fibroblasty; Humans; Fibroblasts; kultivované buňky; Myocardium; Calcium Release Activated Calcium Channels; myokard